144P Loss of BAP-1 influences the activation of p52 and RelB proteins in the Inflammatory microenvironment of uveal melanoma. (15th December 2019) - Singh, M K; Kashyap, S; Singh, L; Pushker, N; Bakhshi, S; Sen, S
Abstract: Background: In recent years, research has focussed on targeted immunotherapeutic therapies in UM are disappointing and questions remain regarding the mechanisms leading to metastases and the tumor's resistance to treatment. Genetic predictors for metastatic tumor behavior is the loss of BRCA1-associated protein 1 (BAP1) expression. NF-κB is a principal coordinator of innate immunity and inflammation and has emerged as an essential endogenous tumor promoter. We hypothesize that genetic changes not only influence the immunological microenvironment but also drive metastasis in UM and that NC-NFκB proteins (p52 & RelB) are the consequence of a highly-inflammatory profile. Methods: In our study, based on the expression of CD3 (infiltrating lymphocytes) and CD68 (infiltrating macrophages), we divided our study cohort into two categories: UM with inflammation and UM without inflammation. Expression of BAP-1 and NC-NFκB proteins (RelB & p52/NFκB2) was evaluated using immunohistochemistry. Real-time PCR was performed on 60 frozen tumor samples. The presence of p52/RelB heterodimer detected by Co-immunoprecipitation in UM with inflammation. Results: In the inflammation group, activation of NC-NFκB proteins found in 82% and 64% of cases while the loss of BAP-1 was observed in 82% of cases. Loss of BAP-1 protein along with activation of NC-NFκB proteins was seen in 70% of cases of the inflammation group. Loss of BAP-1 along with activation of C-NFκB proteins was statically significant with inflammatory factors such as CD34 + (p = 0.036), IL-6 (p = 0.012), LBD>15mm (p = 0.031) and epithelioid cell type (p = 0.027). In the inflammation group fold-change value of RelB (5.21) & NFκB2 (4.65) genes was reduced to 2.85 (RelB) & 2.34 (NFκB2) gene in the non-inflammation group. Mutation of BAP-1 was more frequently seen in the inflammation group than the non-inflammation group. Loss of BAP-1, along with the activation of NC-NFκB proteins, was associated with reduced metastasis-free survival and overall survival (p < 0.05). Conclusion: Our preliminary data reveal that in an inflammation group loss of BAP-1 showed the synergistic role with the activation of NC-NFκB proteins and are the poor prognostic indicators of overall survival. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.